Detection of Voltage-Gated Sodium Channel (VGSC) L1014F knockdown-resistance (Kdr) mutation of Culex quinquefasciatus mosquitoes from Surabaya, Indonesia - INTAN FATMA LISTIANDARI; TEGUH HARI SUCIPTO; SYANANDA ZAHRA FADILA; AHMAD RUDI SETIAWAN; SHIFA FAUZIYAH; SAFIRA MADANIYAH; ERYANTIKA CIPTA DEWI; ANAQI SYADDAD IHSAN; NUNIEK HERDYASTUTI; RUDIANA AGUSTINI; RATIH DEWI SAPUTRI; HARIYONO HARIYONO (Society for Indonesian Biodiversity, 2025)
Abstract. Listiandari IF, Sucipto TH, Fadila SZ, Setiawan AR, Fauziyah S, Madaniyah S, Dewi EC, Ihsan AS, Herdyastuti N, Agustini R, Saputri RD, Hariyono. 2025. Detection of Voltage-Gated Sodium Channel (VGSC) L1014F knockdown-resistance (Kdr) mutation of Culex quinquefasciatus mosquitoes from Surabaya, Indonesia. Biodiveritas 26: 1354-1359. Culex quinquefasciatus mosquitoes are a genus of mosquito that can transmit dangerous viruses to humans through their bites, causing diseases in humans such as lymphatic filariasis, chikungunya, Japanese encephalitis, West Nile fever, encephalitis, and St. Louis encephalitis. Therefore, vector control is needed to suppress the spread of these diseases. An easy and inexpensive method to control the vector is using insecticide. Long-term use of insecticide causes the mosquitoes to gain resistance to it. The phenomenon of mosquitoes becoming resistant to insecticides is referred to as knockdown resistance (Kdr). Kdr occurs due to a mutation in the Voltage-Gated Sodium Channel (VGSC), which is the target site of the insecticide. This mutation leads to the reduced sensitivity of the sodium channel to pyrethroid insecticides. The primary objective of this study was to detect the presence of the Vgsc-L1014F Kdr mutation in C. quinquefasciatus mosquitoes. Samples were obtained from six different locations in Surabaya, East Java, Indonesia. This was determined using a technique known as allele-specific PCR (AS-PCR). DNA was extracted from 23 samples of Culex spp. mosquitoes samples, and the VGSC-L1014F mutation was detected using the AS-PCR technique. The results of this study indicated 13 positive cases for the TTT/TTA mutation and 10 negative cases.